Faktor-Faktor yang Memengaruhi Pengembangan Agrowisata Berbasis Masyarakat di Kawasan Bukit Kelam Kalimantan Barat - Yuhnes Ave Kana; Eva Dolorosa; Novira Kusrini (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Agritourism provides economic and social benefits to local communities, particularly by increasing income and creating employment opportunities. The Bukit Kelam area in Sintang Regency has considerable potential to be developed as community-based agritourism. However, its development still faces several challenges, particularly related to infrastructure and accessibility. This study aims to analyze the determinants influencing the development of community-based agritourism in the Bukit Kelam area of West Kalimantan. The study employed a quantitative approach using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) technique. The results indicate that community-based agritourism development is influenced by several factors, with human resources emerging as the most dominant and significant factor. Institutional support and promotion also have a significant effect in supporting agritourism sustainability, whereas infrastructure and natural resources do not show a significant influence. These findings emphasize that strengthening community capacity and local institutions is the key to the successful development of community-based agritourism in the Bukit Kelam area.